Colossal negative thermal expansion in reduced layered ruthenate - Koshi Takenaka (Nature Portfolio, 2017)
Materials displaying negative thermal expansion have received interest as thermal-expansion compensators. Here, authors report very large total volume change associated with this effect in reduced calcium ruthenates and propose a microstructural origin driven by highly anisotropic thermal lattice expansion.